Research progress of the role of iron homeostasis in ferroptosis in Alzheimer’s disease - Luo Chenliang; Wu Guiyou; Li Zhenzhong; Huang Zhongshi (Guoji laonian yixue zazhi)
Ferroptosis is a distinct type of cellular demise frequently identified in the cerebral tissues of individuals afflicted with Alzheimer’s disease (AD). It contributes to the advancement of several disorders, including dementia, malignancies, and osteoporosis, with the differentially expressed genes associated with it being significantly enriched in Alzheimer’s disease-related genes. Disordered iron homeostasis is a critical mechanism in the process of ferroptosis. Iron is essential in the central nervous system for sustaining mitochondrial energy production, synthesizing myelin and neurotransmitters, and facilitating other fundamental physiological functions. This article offers an extensive analysis of the interactions among many critical elements related to iron homeostasis, ferroptosis, and the common pathogenic mechanisms linked to Alzheimer’s disease (AD).